Physiotherapy Management for Cases of Achilles Tendinopathy in Indonesian Para Athletics Athletes : Case Report - Muhammad Raihan Maulidan; Suryo Saputra Perdana; Amalia Nur Azizah (UNIB Press, 2023)
Achilles tendinopathy is a degenerative process due to excessive and cumulative use of microtrauma with internal and external risk factor. Approximately 52% of runners experience an Achilles tendinopathy (AT) injury during their lifetime. Achilles Tendinopathy can limit Indonesia's athletic performance due to pain on the side of the knee during running, walking and jumping. The aim of this study was to evaluate the physiotherapy management for Achilles Tendinopathy cases in Indonesian para-athletics. This research is a descriptive case studyinvolving one client with participatory observation. The physiotherapy intervention involved modality intervention using Eccentric exercises, ESWT, Stretching, Muscle release, Electrical Stimulation, and Cryotheraphy. The subject of the study was An. B, a 28 year old para athlete with height 182 cm, weight 77 kg, and BMI 23.3 in the ideal category. The patient came to the physiotherapy clinic of NPC Indonesia on 20 August 2023 with complaints of pain and burning in the left leg. Physical examination showed normal results except for pain examination using Numeric Rating Scale (NRS), where silent pain 0/10, tenderness 9/10, and motion pain 7/10 were found. The diagnosis of Achilles Tendinopathy sinistra was confirmed through specific examination. After four physiotherapy sessions Based on the results of studies that have been carried out, ESWT and Eccentric exercise can reduce pain, increase joint range of motion, increase muscle strength, increase ankle stability and improve functional abilities in Achilles tendinopathy patients.